Kelas Sosial dalam Masyarakat Islam Periode Klasik (Dari masa Khulafaur Rasyidin hingga Dinasti Abbasiyah) - Isna Zakiya Nurul Muftaza; Muhammad Ilham Aziz (JSI: Jurnal Sejarah Islam, 2023)
This study aims to determine the social life of Islamic society in more depth and social mobility that occurs in Islamic society. This research is qualitative based on literature, using a sociological approach. In the research process, historical methods are used as research stages which include: verification, interpretation and historiography. The results of this study, First, during the Khulafaur Rashidun era, social class struggles were divided into several groups, namely: the ruling class (elite), Arab Muslims and non-Arabs. Second, during the Umayyad dynasty, the social order of society was divided into four classes, namely: the ruling class, converts, sect members, and slaves. Third, the social order of the people during the Abbasid dynasty underwent significant changes by no longer favoring the Arabs as the top class, and all groups had the opportunity to reach the upper social class. The existence of dynamics in the social class system of Islamic society starting from the Khulafaur Rashidun era to the Abbasid dynasty had an impact on all aspects of the social life of Islamic society.